Analisa Total Bakteri Salmonella spp. pada Produk Ikan Cakalang Asap yang Dijual pada Beberapa Pasar di Kota Ambon - Fiyogi Derandy Alfarego Tuhumury; Martha Kaihena; Cecelia Anna Seumahu (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Skipjack tuna (Katsuwonus pelamis) is one of the dominant capture fisheries products in Maluku. This is supported by the geographical location of the Maluku Islands which are surrounded by the sea. Bacteria are often found in traditional processed fishery products such as smoking fish. This study aims to determine the total bacteria Salmonella spp. and differences in the abundance of Salmonella spp. on smoked skipjack (Katsuwonus pelamis) products sold in several markets in Ambon City. This research is an experimental research. The research was carried out by taking samples with a total of 5 samples from the people's market location, and bacterial calculations were carried out using a dilution technique. Bacteria that have been obtained from the dilution results, then isolated using the quadrant scratch method technique on SSA media (Salmonella Shigela Agar). Bacterial biochemical tests, including: indole test, Methyl-Red test, Voges Proskauer test, citrate test, and Triple Sugar Iron Agar (TSIA) test, and gram staining were performed to confirm/identify the isolated bacteria. The results showed that smoked skipjack sold at Mardika Market was identified as having the total number of Salmonella spp. respectively 6700 CFU/ml and 8400 CFU/ml. The total number of Salmonella spp. on smoked skipjack at Mardika market is different from the results of the calculation of the total bacteria of smoked skipjack sold in modern markets and small hative markets, which did not identify any Salmonella spp bacteria contamination.